2001
DOI: 10.1021/ac0103468
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Biological Conjugate between Antibody and Colloid Au Nanoparticles as Analyte to Inductively Coupled Plasma Mass Spectrometry

Abstract: This paper describes the study of atomization of nanoparticles by inductively coupled plasma mass spectrometry (ICPMS) and developes a novel nonisotopic immunoassay by coupling sandwich-type immunoreaction to ICPMS. The goat-anti-rabbit immunoglobulin G (IgG) labeled with colloidal gold nanoparticles served as an analyte in ICPMS for the indirect measurement of rabbit-anti-human IgG. Matrix effect studies showed the gold signal was not sensitive to the organic matrix. A relatively good correlation (r2 = 0.9528… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
169
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 246 publications
(173 citation statements)
references
References 16 publications
4
169
0
Order By: Relevance
“…Some instruments involved are expensive and require skillful personnel to operate. Many other methods, such as inductively coupled plasma mass spectrometry [9], chemiluminescence [10], electrochemical stripping technique [11,12] have also been reported to measure the amount of colloidal gold in immunoassay or DNA assay. All of these methods require dissolving the gold nanoparticles using bromine or other oxidants * Corresponding author.…”
Section: Introductionmentioning
confidence: 99%
“…Some instruments involved are expensive and require skillful personnel to operate. Many other methods, such as inductively coupled plasma mass spectrometry [9], chemiluminescence [10], electrochemical stripping technique [11,12] have also been reported to measure the amount of colloidal gold in immunoassay or DNA assay. All of these methods require dissolving the gold nanoparticles using bromine or other oxidants * Corresponding author.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the specific activities of biomolecules can be retained when coupling biomolecules to colloidal Au nanoparticles. Au NPs have been applied in ICPMS-based immunoassay since the pioneer works reported by Zhang et al [91] and later by Tanner goupe [92]. Those methods could achieve the detection limits of enzyme-linked immunosorbent assay (ELISA), and their sensitivity can be further enhanced by single particle mode detection [93,94].…”
Section: Labeling and Amplificationmentioning
confidence: 99%
“…Within the field of atomic spectrometry, the concept of elemental labelling with elemental nanostructures was pioneered some years ago by Zhang et al [117] and by Baranov et al [116]. However, this area of research is still of great novelty, with a high potential for future applications and continual development.…”
Section: Direct Inductively Coupled Plasma Mass Spectrometry Analysismentioning
confidence: 99%
“…However, this area of research is still of great novelty, with a high potential for future applications and continual development. In pioneer work, Zhang et al [117] successfully demonstrated the determination of rabbit-anti-human immunoglobulin G (IgG) by ICP-MS using antibodies labelled with colloidal Au NPs. In this work, a sandwich-type immunoreaction was investigated as the format for the measurement of the IgG.…”
Section: Direct Inductively Coupled Plasma Mass Spectrometry Analysismentioning
confidence: 99%